Functionalized MgONanoparticle integrated with PVDF-PEG fibre enhances strength and contaminant separation efficacy - Mohammed Abdulsalam; Mohammed Umar Abba; Ibrahim Babangida Dalha; Badruddeen Saulawa Sani; Katibi Kayode Kamil; Kiman Silas; Ibrahim Garba Shitu; Bello Suleiman (Cleaner Chemical Engineering)
The constituent recalcitrant color pigments and other organic pollutants (such as COD, and MLSS) in palm oil mill effluent (POME) are detrimental, yet the commonly employed conventional remediation method has been inefficient. This study focused on the development of an innovative hybrid membrane designed for efficient decolorization and separation of pollutants. The research involves the incorporation of magnesium oxide (MgO) nanoparticles at a varied loading (0.0–0.75 wt%) into polyvinylidene fluoride (PVDF) and polyethylene-glycol (PEG) hollow-fiber using blending dry-jet wet-swirling phase inversion technique. Initially, the crystallinity and purity of the MgO were examined using X-ray diffraction before the application. Then, morphological characteristics, elemental constituents, mechanical strength, and thermal stability of the resultant membranes were examined using Scanning Electron Microscopy, Energy Diffraction X-ray, tensile loading, and thermogravimetric analysis. The performance results indicated that the membrane sample with the nanoparticles MgO-0.50wt% demonstrated superior mechanical and thermal stability, as well as separation performance. The membrane was able to remove the colorants, COD, suspended solids, total nitrogen, and turbidity by 80.05, 94.10, 98.67, 87.02, and 96.01 %, respectively. Additionally, the sample has the highest flux recovery ratio of 0.929 (or 92.9 %) with a minimal irreversible fouling ratio of 0.071 (or 7.1 %). The regeneration and reusability analysis indicates that at the end of the 4th filtration cycle, the modified membrane (0.50 wt% MgO) exhibited only a 23.22 % reduction in permeability flux. This finding suggests that the nanoparticles MgO 0.50wt% PVDF/PEG sample is a promising technology for POME treatment.